Purification of Mutacin III from Group III Streptococcus mutans UA787 and Genetic Analyses of Mutacin III Biosynthesis Genes - Qi, Fengxia (American Society for Microbiology, 1999)
Previously, members of our group reported the isolation and characterization of mutacin II from Streptococcus mutans T8 and the genetic analyses of the mutacin II biosynthesis genes (J. Novak, P. W. Caufield, and E. J. Miller, J. Bacteriol. 176:4316–4320, 1994; F. Qi, P. Chen, and P. W. Caufield, Appl. Environ. Microbiol. 65:652–658, 1999; P. Chen, F. Qi, J. Novak, and P. W. Caufield, Appl. Environ. Microbiol. 65:1356–1360, 1999). In this study, we cloned and sequenced the mutacin III biosynthesis gene locus from a group III strain of S. mutans, UA787. DNA sequence analysis revealed eight open reading frames, which we designated mutR, -A, -A′, -B, -C, -D, -P, and -T. MutR bears strong homology with MutR of mutacin II, while MutA, -B, -C, -D, -P, and -T are counterparts of proteins in the lantibiotic epidermin group. MutA′ has 60% amino acid identity with MutA and therefore appears to be a duplicate of MutA. Insertional inactivation demonstrated that mutA is an essential gene for mutacin III production, while mutA′ is not required. Mutacin III was purified to homogeneity by using reverse-phase high-pressure liquid chromatography. N-terminal peptide sequencing of the purified mutacin III determined mutA to be the structural gene for prepromutacin III. The molecular mass of the purified peptide was measured by laser disorption mass spectrophotometry and found to be 2,266.43 Da, consistent with our supposition that mutacin III has posttranslational modifications similar to those of the lantibiotic epidermin.